Detection and characterization of a coxsackievirus B2 strain associated with acute meningoencephalitis, Brazil, 2018 - Ivanildo Pedro de Sousa Jr; Raiana Scerni Machado; Fernanda Marcicano Burlandy; Edson Elias da Silva (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract Although different etiological agents can cause acute meningoencephalitis, this syndrome is usually associated with viruses. Among these, enteroviruses play a significant role. Here, we describe a fatal case of meningoencephalitis in a previously healthy teenager. Real-time RT-PCR and cell culture assays were performed with serum and cerebrospinal fluid (CSF) from a clinically diagnosed meningoencephalitis case that occurred in Rio de Janeiro State, Brazil. Coxsackievirus B2 (CVB2) was identified. Phylogenetic analysis revealed that the identified CVB2 was genetically related to strains known to cause neurological diseases. This case highlights the importance of continuous laboratory surveillance of central nervous system infections.